Exploration of Papaya Leaf Bioactive Compounds as Antimalarials Using Network Pharmacology, In Silico, and Learning Resources - Giska Ulya; Arwansyah Arwansyah; Sitti Nuryanti; Sitti Rahmawati; Dewi S. Ahmar (Universitas Tadulako, 2026)
Papaya leaves (Carica papaya Linn.) are plants with many benefits due to their active compounds, which can inhibit the growth of malaria parasites. Malaria is an infectious disease caused by the Plasmodium sp. parasite. This study aims to determine the potential of active compounds from papaya leaves (Carica papaya Linn) as an alternative treatment for malaria caused by Plasmodium sp. parasites. This research employs network pharmacology to identify potential protein targets for antimalarial drug development. Also, it employs molecular docking methods to predict the interaction of active compounds such as Carpaine, α,α-Trehalose, Diacylglycerol, N-octanoyl-homoserine lactone, and N-lauroyl glycine with receptors such as Dihydrofolate Reductase-Thymidylate Synthase (DHFR-TS), Falcipain, Dipeptidyl Aminopeptidase, Glucose Transporter (PfHT), Peroxiredoxin (Prx), Dihydroorotate Dehydrogenase (DHODH), Plasmepsin, Rhomboid Protease, Phosphoethanolamine N-Methyltransferase (PfPMT), Enoyl-Acyl Carrier Protein Reductase (ENR), and Apical Membrane Antigen 1 (AMA1). Based on the network pharmacology results, 94 protein targets were identified. Molecular docking results for 8 compounds revealed that 5 compounds had potential as antimalarial agents. From these five compounds, five protein targets were selected for each compound based on their high binding affinity. Among the five compounds, Carpaine was identified as having the highest binding affinity with the Dihydrofolate Reductase-Thymidylate Synthase (DHFR-TS) protein, indicating significant potential for drug development, particularly for malaria prevention. This study also contributes as a scientific learning resource in the fields of chemistry, pharmacy, biotechnology, and health sciences. Therefore, a video-based learning medium was developed and validated in this study, yielding a score of 83.63%, indicating that the learning video is highly suitable as a learning resource.